2021
DOI: 10.1200/jco.2021.39.15_suppl.e13609
|View full text |Cite
|
Sign up to set email alerts
|

National survey on the effect of oncology drug shortages in clinical practice: A Hematology Oncology Pharmacy Association (HOPA) survey.

Abstract: e13609 Background: Drug shortages are a clear and growing challenge. Prominent shortages included oncology medications and supportive care products essential for the care of cancer patients. Oncology drug shortages often result in disruptions in the timing of chemotherapy treatments, alterations in the dose or regimen administered, or even missed doses when alternative agents are unavailable. The purpose of this survey was to characterize the impact of oncology drug shortages across the United States, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…33% in 1 year alone. 43 This resulted in increased costs to organizations, and more than 75% of respondents said that these shortages altered therapy in some way. Even more alarming is that hematologic malignancies are often most affected by shortages.…”
Section: Best Practices To Use the Limited Supply Optimallymentioning
confidence: 99%
See 1 more Smart Citation
“…33% in 1 year alone. 43 This resulted in increased costs to organizations, and more than 75% of respondents said that these shortages altered therapy in some way. Even more alarming is that hematologic malignancies are often most affected by shortages.…”
Section: Best Practices To Use the Limited Supply Optimallymentioning
confidence: 99%
“…A recent survey of oncology pharmacists done by the Hematology/Oncology Pharmacy Association (HOPA) found that 63% of institutions reported at least one drug shortage in the past month, an increase of > 33% in 1 year alone. 43 This resulted in increased costs to organizations, and more than 75% of respondents said that these shortages altered therapy in some way. Even more alarming is that hematologic malignancies are often most affected by shortages.…”
Section: Best Practices To Use the Limited Supply Optimallymentioning
confidence: 99%